PERKEMBANGAN MEDIA PEMBELAJARAN KINCIR CIPURAK (KARAKTERISTIK PUISI RAKYAT) MATERI PUISI RAKYAT KELAS VII MTS AL-MUHTADUN JABUNG TALUN BLITAR - Nurani, Aldina Dwi; Hermawan, Agus; Hadi, Saptono (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This research is based on the challenges faced by grade VII students in understanding folk poetry materials, including rhymes, poems, and gurindam, often due to less interesting learning approaches and the absence of adequate interactive media. To overcome these problems, development research is carried out to produce learning media that is relevant and can facilitate student understanding. The 4D development method (Define, Design, Develop, Disseminate) was chosen as the framework for this research. The implementation of the learning media named "Kincir Cipurak" was carried out for grade VII students in one of the junior high schools in East Java. Before being widely implemented, this media went through a validation stage involving material experts, media experts, and subject teachers to ensure its feasibility of use. A limited trial has also been carried out on 16 students. The results of the study show that the learning media "Kincir Cipurak" has proven to be effective in improving students' understanding of folk poetry materials. Assessments from subject matter experts, media experts, and subject teachers categorize this media as "very feasible" to be implemented, with a high average percentage of feasibility in terms of appearance, language, and feasibility of material content.